Isolation, identification and molecular characterization of contagious ecthyma virus from goat and sheep - Alam, Jahangir; Alam, Md Shahin; Giasuddin, Md; Monoura, Papia; Samad, Md Abdus; Faruque, Md Hasan Al; Rahman, Md Bahanur; Khan, Md Shahidur Rahman; Ershaduzzaman, Md; Taimur, MJFA (Bangladesh Journal of Livestock Research, 2016)
Contagious ecthyma (CE) is one of the most widespread viral diseases; primarily affect goat and sheep but also reported from human, reindeer, musk ox, dog, cat, red squirrel etc. The disease is caused by contagious ecthyma virus (CEV) and he virus is circulating in Bangladesh. Present study was aimed at isolation, identification and molecular characterization of the CEV circulating in Bangladesh. A total of 13 samples (scab materials; 11 from goat and 2 from sheep) were collected from three different farms of Sylhet and Dhaka divisions followed by processing for virus detection by PCR and isolation in Vero cell. Four different sets of primers were used targeting four different genes of CEV. Of these samples, 10 (8 from goat and 2 from sheep) were found positive by PCR. From these positive samples three viruses were isolated. Sequencing of different genes of several CEV isolates has been done directly from PCR product using automated DNA sequencer 3010 Genetic Analyzer available at the National Reference Laboratory for Avian Influenza (NRL-AI), Bangladesh. Bangladeshi isolates were found to have 95-99% identity to each other. When compared to viruses from other countries, high homology (92-96%) was observed to viruses from New Zealand and India, and phylogenetically clustered with them. This is the first report of molecular characterization, though partial, of CEV in Bangladesh. Bangladesh J. of Livestock Res. 19(1-2): 97-106, Jan-Dec 2012